A clinical study to evaluate the effectiveness of using transpositioned local flaps in large lower lip loss reconstruction - محمود مزن; يعقوب حكمت (Latakia University Journal -Medical Sciences Series, 2022)
This study aimed to evaluate the efficacy of the multistages transpositioned local flaps harvested from the same lip in lower lip large loss reconstruction and restore the anatomical aspects and function. The research sample consisted of 10 cases submitted to the Department of Oral and Maxillofacial Surgery at Tishreen University Hospital, suffered from loss of lower lip larger than 1\3 of the lip width. Their ages between 9-68 years old. The study was conducted between 2109-2022. The studied variables was; the lip height pre and post surgical operative and the microstomia. The results showed that there were statistically significant differences in the lip height between pre and post operative, and absence the microstomia in all patients. Using the trans positioned local flaps significantly improved the lip height post operative which improved the aesthetic and function aspects in all patients. This protocol didn’t affect microstomia and there was good results in the ability to open mouth and eat naturally in all patients.